Pengaruh Pemerataan Pendapatan Terhadap Pertumbuhan Ekonomi Provinsi Sumatera Barat Periode 1987-2020 - Maulia Usni; Faidil Tanjung; Yonariza Yonariza (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Indonesia's Economic Equality Policy which aims to increase economic growth and income equality and strengthen each other in economic development in Indonesia makes an Indonesian step in supporting the theory developed by Simon Kuznets so that sustainable economic development can be realized. West Sumatra Province for the 2020 period has an increasing income distribution condition, but economic growth conditions have decreased in the 2020 period. In supporting the policies of West Sumatra Province, it is important to see how the influence of income equality and economic growth in West Sumatra Province. This study used secondary data for the 1987-2020 period with a type of time series data sourced from BPS West Sumatra and BPS Indonesia. The data analysis used is VECM (Vector Error Correction Model) using Eviews 12. The results of the study found that economic growth affects income equality. In the short and long term, it has a positive influence, meaning that the economic growth that occurs causes the realization of income equality in West Sumatra Province. The researchers suggested that the West Sumatra Provincial government increase the economic growth of West Sumatra Province in support of the Economic Equality Policy in Indonesia